PENGGUNAAN METODE RESOURCE BASED LEARNING ( RBL ) DALAM UPAYA MENINGKATKAN HASIL BELAJAR PAI SISWA MATERI HUKUM BACAAN QALQALAH DI KELAS VIII.2 SMP NEGERI 3 PULAU RAKYAT TAHUN PELAJARAN 2018/2019 - Yenni Sri Wahyuni (Universitas Islam Negeri Sumatera Utara Medan, 2020)
The study aims to determine whether the use of Resource Based Learning (RBL) Method Can Improve Student Learning Outcomes of QAI Qalqalah Material in Class VIII.2 SMP Negeri 3 Pulau Rakyat Academic Year 2018/2019. The subjects of this study are students of VIII.2 SMP Negeri 3 Pulau People 2018/2019 Academic Year with a total of 35 people. This research method is observation and test. The research instrument used in this study was the observation sheet and daily tests.From the management of the data obtained the average value obtained by students in the first cycle of 56.1. Of the 35 students, 19 students (54.3%) had completed learning while 16 students (45.7%) had not yet completed learning. Then in the second cycle an increase in the average value to 73.1. Of the 35 students, 29 students (82.9%) had experienced mastery learning, while 6 more students (17.1%) had not succeeded.Based on the increase in grades starting from the initial test, cycle I and cycle II can be said that using the method of Resource Base Learning (RBL) can improve student learning outcomes of PAI in class VIII.2 SMP Negeri 3 Rakyat Island 20182019 Academic Year on Qalqalah material.